Manajemen Strategis Kepala Sekolah dalam Pembinaan dan Peningkatan Prestasi Siswa di SMP Negeri 34 Sarolangun - Wahyuni Wahyuni (JMiE (Journal of Management in Education), 2023)
This study aims to describe the principal’s strategies in fostering and developing student achievement at SMP Negeri 34 Sarolangun. The research employs a qualitative descriptive approach, utilizing both primary and secondary data sources. Primary data were obtained directly through interactions with informants, while secondary data were collected from relevant school documents and archives. Data were gathered through observation, in-depth interviews, and documentation to obtain a comprehensive understanding of the principal’s strategies in student development. The results indicate that the principal implements a direct coaching strategy to enhance student achievement. This strategy involves conducting regular coaching sessions for students, monitoring teacher performance, and supervising student activities and progress in both academic and non-academic areas. The principal also actively identifies students’ potentials, interests, and talents through extracurricular programs and other supportive school activities. The findings suggest that the principal’s direct involvement in the student development process has a positive impact on students’ motivation and achievement. Therefore, it is recommended that participatory and continuous coaching strategies be further developed to create a conducive school environment that supports optimal student achievement.